Aerodynamic stability of airfoils in lift-type vertical axis wind turbine in steady solver. (October 2017) - Li, Jinyi; Cao, Yang; Wu, Guoqing; Miao, Zifan; Qi, Jiawei
Abstract: This paper presents a method examining static forces and moment of airfoil in steady solver. Aerodynamic stability is one subject that many scholars have begun to realize very crucial for design and daily operation. Fundamentals of aerodynamics were firstly scrutinized concerned about lift, drag and moment. Then steady simulation solver is set up instead of transient solver because we would like to examine airfoil without the effect of vortex motion, temporarily focus on static forces on airfoil. Dependent variable include cl, cd and cm of three airfoils, FLAT PLATE, NACA0012 and NACA23012 at TSR = 0, 2, 5 and 7. Stability is characterized by deviation and fluctuation at 360 degrees of azimuth position. We found that FLAT PLATE showed most deviation and fluctuation as an example of airfoil for VAWT. NACA0012 representing symmetric airfoil has more stable cm at whole time and cd just at TSR of 2 and 5. NACA23012 representing cambered airfoil has more stable cl all phases of running. Highlights: Aerodynamic stability of airfoil used in VAWT has been examined, instead of only focusing on energy coefficient. Steady method has been applied in order to focus on static forces and moment on airfoil. Speed synthesis on airfoil has been applied according to the steady method. Deviation and fluctuation have been introduced to analyze stability of airfoil.